2010
DOI: 10.17159/2078-516x/2010/v22i2a314
|View full text |Cite
|
Sign up to set email alerts
|

The <i>COL5A1</i> gene and musculoskeletal soft-tissue injuries

Abstract: Background. It has been shown that there is an association between various genetic variants and Achilles tendon injuries as well as anterior cruciate ligament (ACL) ruptures. Among other variants the BstUI restriction fragment length polymorphism (RFLP) within the COL5A1 gene has been shown to be over-represented in asymptomatic participants when compared with those with chronic Achilles tendinopathy, and in asymptomatic female participants when compared with those with ACL ruptures. The male asymptomatic cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The functional COL5A1 Sp1 binding site polymorphism - BstUI RFLP, known also as: rs 12722, C/T is associated with a number of sport injuries. This polymorphism was detected in a physically active Caucasian population in South Africa ( Posthumus et al, 2010 ).…”
Section: Introductionmentioning
confidence: 96%
“…The functional COL5A1 Sp1 binding site polymorphism - BstUI RFLP, known also as: rs 12722, C/T is associated with a number of sport injuries. This polymorphism was detected in a physically active Caucasian population in South Africa ( Posthumus et al, 2010 ).…”
Section: Introductionmentioning
confidence: 96%
“…This highlights the possibility that there is a subset of polymorphisms that protect individuals from a specific injury and that matching controls with cases for all possible confounding factors, such as exposure to the same sport, level of training, among others, is an important consideration in future research. 46 This is currently a limitation in the GWAS studies published to date since these subsets of polymorphisms would not be identified in GWAS where the controls represent the general population. 47 In addition to the CC genotype, the TT genotype was also independently associated with reduced risk of Achilles tendinopathy in the Australian (Aus) population (Figure 2).…”
Section: Achilles Tendon Injuries and Ctsmentioning
confidence: 99%
“… 42,43,45 Interestingly, when compared to the general population the CC genotype was over‐represented in the asymptomatic physically active controls with no history of Achilles tendon injuries, while the CC genotype of the Achilles tendinopathy group was similar to the general population. This highlights the possibility that there is a subset of polymorphisms that protect individuals from a specific injury and that matching controls with cases for all possible confounding factors, such as exposure to the same sport, level of training, among others, is an important consideration in future research 46 . This is currently a limitation in the GWAS studies published to date since these subsets of polymorphisms would not be identified in GWAS where the controls represent the general population 47 …”
Section: Multifactorial Phenotypesmentioning
confidence: 99%